Membedah Konten Kecerdasan Visual: Etika dan Implementasi - Thoriq, Miftah Jabalut; Khoerunnissa, Nanda Aulia; Nadin, Salwa Putri; Salsabila, Nofia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of artificial intelligence (AI) technologies, especially in the field of visual intelligence, has brought great transformation in various aspects of life, such as education, law, healthcare, and digital media. Although visual AI presents convenience and efficiency, the technology also poses serious ethical problematics, including privacy issues, reality manipulation, algorithmic bias, as well as the potential for dehumanization in visual representation. This study aims to analyze the potential, implementation, and ethical challenges of visual intelligence with a qualitative approach through a literature study against ten scientific journals from different disciplines. The results of the study indicate that the utilization of visual AI can be justified as long as it does not conflict with humanitarian values, Islamic spirituality, and the principle of Pancasila. The Islamic perspective emphasizes the importance of the use of technology within the framework of maqÄá¹£id al-syarÄ«â€˜ah and the principles of saddu al-dzarÄâ€™i, while Pancasila becomes the ethical framework of the nation that guides the equitable and civilized application of technology. This study recommends the importance of regulation and multidisciplinary collaboration in order to steer the development of visual AI to be not only technically intelligent, but also ethical and dignified.